PENDIDIKAN ANDRAGOGI DALAM PERSPEKTIF PENDIDIKAN ISLAM (Analisis Surat Al-Kahfi Ayat 70-82) - Nur Afni, Nur Afni (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2024)
The purpose of this study is to explain andragogy education contained in al-Kahf verses 70-82, and to describe the implementation of andragogy education contained in sura al-Kahfi verses 70-82 in Islamic education in the contemporary era. Literary qualitative research using the mawdhūi method with primary data sources of interpretations of Tarbawi, al-Maraghi, Munir, and secondary data sources of books and journals in andragogy education and Islamic education. The results of the research are 1) andragogy education in al-Kahfi verses 70-82 of the prophet Khidir as an educator has good physical and spiritual abilities in teaching the prophet Musa, Prophet Musa as a student has academic ethics towards teachers, ethics of dialogue, there is educational value and already applied. 2) Application of andragogy education in al-Kahfi verses 70-82 in the present era or the era of information and communication technology, namely the method of providing convenience, the question and answer method, the demonstration method, the Targhib wa Tarhib method, the evaluation method and games combined using the Youtube application, video conference, Voice note, Google slide, Padlet, Google Form, Google Jamboard, Ideaboardz, Webex meet, targib wa tarhib, Quizizz, Kahoot and Mentimeter, visual, audio and visual audio based technologies can be applied